How Business Customers Judge Solutions: Solution Quality and Value in Use - Macdonald, Emma K.; Kleinaltenkamp, Michael; Wilson, Hugh N. (Journal of Marketing, 2016)
Many manufacturers look to business solutions to provide growth; however, success is far from guaranteed, and it is unclear how such solutions can create superior perceived value. This article explores what constitutes value for customers from solutions over time—conceptualized as “value in use”—and how this arises from quality perceptions of the solution's components. The authors develop a framework for solution quality and value in use through 36 interviews combining repertory grid technique and means-end chains. The findings significantly extend the extant view of quality as a function of the supplier's products and services, and show that customers also assess the quality of their own resources and processes, as well as the quality of the joint resource integration process. The authors report that value in use corresponds not just to collective, organizational goals but also to individuals’ goals, a finding that strongly contrasts with prior research. Four moderators of the quality–value relationship demonstrate customer heterogeneity across both firms and roles within what the authors term the “usage center.” When shifting toward solutions, manufacturers require very different approaches to market research; account management; solution design; and quality control, including the need for value-auditing processes.